2012
DOI: 10.3988/jcn.2012.8.3.184
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal Manometric Dysfunctions in Newly Diagnosed, Early-Stage Parkinson's Disease

Abstract: Background and PurposeAnorectal dysmotility is common in advanced Parkinson's disease (PD), but there have been few evaluations in newly diagnosed PD patients.MethodsWe conducted anorectal manometric evaluations in 19 newly diagnosed, drug-naïve, early-stage PD patients. All of the PD patients were questioned regarding the presence of anorectal symptoms.ResultsAnorectal manometry was abnormal in 12 of the 19 patients. These abnormalities were more common in patients with more severe anorectal symptoms, as meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…This functional outlet obstruction may cause both excessive straining and a sense of incomplete emptying, or sometimes, may induce painful defecation. 1517 Another mechanism appears to involve the colonic musculature, which induces a slow passage of feces through the colon 14. Several studies have demonstrated considerably prolonged mean colonic transit time in PD patients 18…”
Section: Discussionmentioning
confidence: 99%
“…This functional outlet obstruction may cause both excessive straining and a sense of incomplete emptying, or sometimes, may induce painful defecation. 1517 Another mechanism appears to involve the colonic musculature, which induces a slow passage of feces through the colon 14. Several studies have demonstrated considerably prolonged mean colonic transit time in PD patients 18…”
Section: Discussionmentioning
confidence: 99%
“…Constipation is a common nonmotor symptom of neurological conditions [1] including Parkinson's [2, 3]. Constipation is the most common gastrointestinal complaint reported in people with Parkinson's (PwP) and is estimated to impact 27–67% of all sufferers [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PD often experience nonmotor symptoms to include orthostatic hypotension, urinary urgency, sexual dysfunction, disorders of sleep, psychosis, depression, and dementia. 7 With advancing PD, an inadequate fluid intake, dehydration, and poor intake complicate constipation. The cause of constipation is slow or impaired colonic transit time (CTT), weak abdominal strain (from rigidity and reduced axial muscle contractility), and abnormal motor control of the anal sphincter.…”
Section: Pd and Constipationmentioning
confidence: 99%